UNEMPLOYMENT HYSTERESIS IN POST-RECESSION ECONOMIES - Abraham, Bejoy (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Unemployment hysteresis describes the phenomenon where temporary spikes in unemployment during recessions lead to persistent increases in the natural rate of unemployment, challenging traditional equilibrium models. This occurs through multiple channels: skill depreciation among long-term unemployed workers reduces employability; psychological demotivation and eroded job-search intensity follow prolonged joblessness; and institutional factors like wage stickiness create labor market rigidities. Crucially, historical unemployment rates influence future structural unemployment, meaning aggregate demand shocks can permanently scar an economy. Empirical analyses confirm hysteresis effects across advanced economies. OECD data reveals that disinflationary periods correlate with large, lasting increases in natural unemployment, while inflationary run-ups associate with declines. Post-2008 evidence shows the U.S. natural rate rose by 0.16 percentage points for every 1-point actual increase, with slower reversion after negative shocks. The Great Recession exemplified this: despite recovery, unemployment remained elevated for years due to skill erosion and depressed hiring. Monetary policy critically determines hysteresis severity. When the zero lower bound constrains central banks (e.g., post-2008), economies risk "unemployment traps" where skill loss perpetuates high unemployment. Timely, aggressive accommodation mitigates scarring by preserving labor force attachment, whereas delayed responses amplify permanent damage. Fiscal interventions—job training, wage subsidies, and structural reforms—complement monetary policy by addressing skill mismatches and institutional rigidities. Cross-country variation highlights that flexible labor markets and robust active policies reduce persistence, as seen in faster recoveries outside the Eurozone periphery